Effects of dietary Bacillus pumilus on growth performance, innate immunity and digestive enzymes of giant freshwater prawns (Macrobrachium rosenbergii). (12th March 2019) - Zhao, Chenze; Zhu, Jinyu; Hu, Juntao; Dong, Xiaojing; Sun, Longsheng; Zhang, Xiaojun; Miao, Shuyan
Abstract: The present study was conducted to investigate the effects of Bacillus pumilus on the growth performance, innate immunity and digestive enzymes of the giant freshwater prawn, Macrobrachium rosenbergii . Prawns (mean weight: 1.81 ± 0.01 g) were fed different levels of B .  pumilus at doses of 0, 1 × 10 7, 1 × 10 8 and 1 × 10 9 CFU/g to produce one control group and three experimental groups (G1, G2 and G3), respectively. After a 60‐day experimental feeding period, the results showed that the final weight, weight gain rate (WGR) and specific growth rate (SGR) were significantly higher in experimental groups than in the control ( p  < 0.05), whereas these improvements did not differ significantly ( p  > 0.05) among experimental groups. The improvements in phagocytic activity, respiratory burst (RBs) activity and the activity of catalase (CAT), nitric oxide synthase (NOS) and acid phosphatase (ACP) were significantly higher in G2 and G3 than in the control and G1 ( p  < 0.05). Further, the activity of CAT, NOS and ACP significantly increased with an increase in the dietary level of B. pumilus ( p  < 0.05). The activity of phenoloxidase (PO) in G3 was significantly higher than that in the control ( p  < 0.05). The activity of amylase was significantly higher in the groups G2 and G3 than that in the control group. G3 improved the activity of protease compared with the control ( p  < 0.05). In conclusion, the results of this study indicated that the potential use of B. pumilus at a dose of 1 × 10 8 CFU/g feed could improve the growth, immunity and digestive enzymes of M. rosenbergii .